Pessoa e Saramago – diálogo de eruditos - Wojciech Charchalis (Studia Romanica Posnaniensia, 2013)
Portugal has been always on the periphery of the main history, also the literary history, so that in order to go out of the localism of the poetry, F. Pessoa created a group of poets whose purpose was to create a modern Portuguese poetry. José Saramago, going in the same direction dozens of years later, seems to have been a slave of the concept of portugality created by F. Pessoa. Both authors are interconnected in a surprising way, as if one could not exist without the other. Saramago’s novels are influenced by Pessoa’s literary creation, like a great part of the contemporary Portuguese literature, both poetry and prose. The paper depicts the influence of F. Pessoa on J. Saramago and discusses the phenomenon of portugality and the role of Pessoa in its formation.